TEACHING STORY TELLING USING MIND MAPPING IN SPEAKING CLASS ( A Case Study in Intermediate Levels at LKP Nuansa Jaya ( English Course ) - Nurhayati Nurhayati (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2011)
The study investigated the use of using mind mapping in storytelling to help learners in conducting speaking skill. This study employed a case study method, and the data were collected by ways of observations, questionnaires, and interviews. The researcher observed and the activities in the classroom, and transcribed the result. It is then recommended that a further study is conducted focusing on wider area on similar contexts, also in different contexts and different levels. Furthermore, conducting teaching and learning process, in different context, varied strategies are suggested to apply in the classroom. However, a further study is recommended in order to find out whether the mind mapping strategy can be used to enhance learners’ English skills in different context and levels.Key words: teaching, speaking, mind mapping